Improving the Islamic Education Learning Quality through Classroom Management in Madrasah Ibtidaiyah - Moh. Mahfud; Akhmad Zakki Abd. Razak; Waleed Yahya Gahlan (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2024)
This research aims to describe classroom management practices and teachers' efforts to improve the quality of Islamic religious education learning in Madrasah Ibtidaiyah. A qualitative approach with a case study method was employed, utilizing observation, interviews, and document studies for data collection. Data analysis involved reduction, presentation, validation, and conclusion drawing. The findings reveal that classroom management by teachers includes preparation of essential teaching skills.  Teachers enhance classroom management through various approaches: discipline, reward and punishment, teaching, attitude, and group process. This research contributes to the academic understanding of classroom management implementation in Islamic religious education at the Madrasah Ibtidaiyah level.  In Islamic education, classroom management is a crucial skill for educators, aligning with the Prophet Muhammad’s SAW emphasis on purposeful, precise, and thorough efforts in teaching.